Intranational Home Bias in Trade - Wolf, Holger C. (The Review of Economics and Statistics, 2000)
A number of recent studies have found intranational trade to be excessive compared to international trade, based on a gravity specification. The preferred explanation for this finding has been the presence of formal and informal trade barriers, with associated welfare consequences. If such barriers were indeed the sole culprit, home bias should not exist on the subnational level. We find, however, that home bias is present within U.S. states, suggesting the presence of other causes of excessive home trade.